Environmental protection and disaster risks selected papers from the 1st International Conference on Environmental Protection and Disaster Risks (EnviroRISKs) - Dobrinkova, Nina; Gadzhev, Georgi (Switzerland Springer, 2021)
Environmental protection and disaster risk topics are challenging fields, that scientific world is trying to address as much as it can. Earthquakes, floods, fires, droughts, blizzards, dust storms, natural releases of toxic gases and liquids, diseases and other environmental variations affect hundreds of millions of people each year. Many disaster events are triggered by human activities. Dealing with these problems will require systems thinking and integrating multidisciplinary science. Actions in these directions are taken more and more in the recent years by political bodies, NGOs and scientific groups trying to find sustainable solutions for the future generations. Every point of view matter when it comes to our global home – The Planet Earth. The book is a comprehensive collection of extended contributions from the International Conference on “Environmental protection and disaster RISKs”, Sofia, Bulgaria, 2020, held as online participation event in the period 29th–30th September 2020. This book presents recent advances in the topics: air pollution, climate and health, natural hazards and risks, water resources, human activities and management and informatics, remote sensing, high-performance computing and GIS for environmental monitoring and management. The book is focused on important large-scale applications like Environmental and Climate Modeling, Computational Optimizations and Algorithms for specific hazard situations.
Effects of satellite data assimilation in air quality modelling in Bulgaria -- Degree-days and Agro-meteorological Indices in CMIP5 RCP8.5 Future Climate-Results for Central and Southeast Europe -- Assessment of the Joint Quantiles of Temperature and Precipitation in CMIP5 Future Climate Projections over Europe -- Coastal boundary-layer characteristic during night time using a long-term acoustic remote sensing data -- Climatological study of extreme wind events in a coastal area -- Anthropogenic and Solar Influence on Temperature over Bulgaria -- Chemical Characteristics of Precipitation and Cloud water at High Elevation site in Bulgaria -- Performance of two operational chemical transport models for particulate matter concentrations in Bulgaria.
Electronic reproduction
Keywords: Environmental protection -- Congresses; Hazard mitigation -- Congresses; Environmental protection; Electronic books